DAKWAH DAN PERDAMAIAN DALAM PUISI ARAB - Walidin, Muhammad; Sukirman, Uki; Fatimatul Djamilah, Wulan Indah (BINA' AL-UMMAH, 2020)
The research entitled Da'wah for Peace in Arabic Poetry aims to answer the question of the contribution of poetry in creating peace. Primary data is taken from the poetry anthology of Zuhair bin Abi Salma and al-A'sya Qais. The data are then analyzed using a semiotic approach with the theory of Michel Riffaterre. The results showed that heuristically the two poems can be understood as a language phenomenon that displays "meaning". This linguistic information can be interpreted as a sequential arrangement of information. Zuhair's poetry features praise for Haram bin Sinan and Harist bin Auf, the condition of Zuhair's faith, and the destructive effects of war. Meanwhile, al-A's poetry displays praise for Mukhalliq who is very compassionate. Retroactively, both poems convey a deeper "significance". Signifier and signified show indexical, iconic, and symbolic relationships. Zuhair bin Abi Salma as a poet has exemplified himself as an agent of peace who could resolve the 40-year dispute between the klan of Abs and Zubyan. This shows that Zuhari as a person who is qualified with his poetry is able to lead public opinion to do good things. Likewise al-A's with his poetry. He has also been able to resolve Mukhalliq's troubled problem. Al-A's poetry is able to change the conditions of conflict to  peace for the poor life of Mukalliq and his family.